(3GdOQI ajeG jLH GYJbGOIs - (3Ydj Hf CMeO Hf SYjO Hf MRe GdXGgQj, GHf MRe , CHh eMeO ,J (B456 (3g` s
(3ChdgG (B:s
(3CeG HYO YUefG Gddg hEjGce ef HdGA GdOfjG hHdGA GdGNQI hSde dfG GOjGffG aPdc GYXe GdSdGeI aEffg PcQfG ai ZjQ ehVY ef cJHfG deG jdRe Ggd GdJejjR GYJbGOg hGdbhd Hg s
(3BNQgG (B:s
(3hjbhdhf Gf SjFI hGMOI JHWd LejY MSfGJ GdeSde hJNQLg ef GdGSdGe hCeJfG Ydi GdGSdGe hGdSfI Gejf s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B254 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B17 - (3U (B16s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg , JQeje s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeSLO GdGbUi HGdbOS (B(2779(3)) s
Keywords: (3GdJhMjO hGdedd hGdfMds